West Nile virus - Angenvoort, Joke Henriette (Tierärztliche Hochschule, 2016)
The flavivirus West Nile virus is an arbovirus, which is maintained in an enzootic cycle between mosquitos and birds which are the reservoir hosts and spread the virus to new regions. In recent years, WNV has spread to new geographic regions and is now endemic on almost every continent. Periodic outbreaks with neurologic disease and deaths amongst humans, equines and birds occur in Europe and the U.S. Raptors are particularly vulnerable to WNV infection, in addition to passerine species. To characterize the pathogenesis of lineage 1 NY99 isolate and lineage 2 goshawk Austria 2009 isolate for large falcons we experimentally infected two falcons each (gyrfalcons and hybrid falcons of this species) with low, intermediate and high doses of the two isolates. Diseased animals infected with both lineages showed marked, nonspecific general disease symptoms. All birds developed substantial viraemia and shedding of viral genome via the oral and cloacal route for two to three weeks. High viral loads were detected especially in brain, spleen, kidney and heart. All of the infected falcons seroconverted after WNV infection. Main pathological alterations were splenomegaly, non-suppurative myocarditis, non-suppurative meningoencephalitis and necrotizing arteritis. In conclusion, these results show that WNV is highly virulent for large falcons and that they are potential reservoir hosts for this flavivirus. No approved veterinary WNV vaccine is available for use in large falcon species. We evaluated safety, immunogenicity and efficacy of two commercial equine vaccines (Duvaxyn® WNV, inactivated whole virus and Recombitek® rWNV, recombinant canarypoxvirus expressing WNV prM an E proteins) and two DNA vaccines at research level (DNA-1 and DNA-2, plasmids coding for E protein ectodomain of lineage 1 and 2 WNV isolates) in large falcons using different vaccination protocols (gyrfalcon, saker falcon, peregrine falcon and hybrids of these species). The inactivated vaccine was tolerated well, while the recombinant vaccine revealed ...